The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s00217-012-1894-5
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive peptides generated in an enzyme membrane reactor using Bacillus lentus alkaline peptidase

Abstract: Bacillus lentus alkaline peptidase (BLAP) was used for casein (CN) hydrolysis in an enzyme membrane reactor (EMR) because it was found that BLAP was competitively inhibited by its products. The employed membranes had different molecular weight cut-offs (MWCO 1, 5 and 10 kDa). It was shown that the productivity of the EMR could be significantly improved (28 %) in comparison with batch hydrolysis under the same conditions after 20 h. All resulting EMR peptide mixtures showed a homogenous peptide pattern in HPLC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 37 publications
(35 reference statements)
0
25
0
Order By: Relevance
“…The kefir peptides VYPFPGPIPN and QEPVLGPVRGPFPIIV were identified by Eisele et al [124] as strong antioxidative peptides and weak ACE inhibitors. Other peptide sequences identified in commercial dairy products had previously been described as antioxidant BPs (Table 3).…”
Section: Antioxidant Peptides Identified In Commercial Fermented Dairmentioning
confidence: 99%
“…The kefir peptides VYPFPGPIPN and QEPVLGPVRGPFPIIV were identified by Eisele et al [124] as strong antioxidative peptides and weak ACE inhibitors. Other peptide sequences identified in commercial dairy products had previously been described as antioxidant BPs (Table 3).…”
Section: Antioxidant Peptides Identified In Commercial Fermented Dairmentioning
confidence: 99%
“…[11] In addition, kefir contains abundant natural bioactive peptides and exhibits a variety of biological activities, such as angiotensin-converting enzyme inhibitory, antithrombotic, mineral binding, opioid, immunomodulating, antimicrobial, and anti-oxidative effects. [12][13][14][15] The present study evaluated the anti-obesity effect of kefir peptides. We fed animals a moderately high energy diet containing 8% soybean oil and 44% sweetened condensed milk supplemented with kefir peptides for 8 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…The ACE inhibition of the peptide mixtures was dependent on the molecular weights (MWs) of the membranes (Eisele et al . ). The results showed that the migration pattern for proteins in the molecular weight ladder, control RSM and traditional fermented RSM and fermented RSM with agitation by bioreactor, respectively (Figure b,c).…”
Section: Resultsmentioning
confidence: 97%